Analysis of DPRD Performance in Implementing the Right of Initiative in the Formation of Regional Regulations - Rusli La Isi; La Ode Muhammad Ricard Zeldi Putra; Mashendra (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study aims to analyze the performance of the Buton Regency Regional People's Representative Council (DPRD) in implementing the right of initiative in the formation of Regional Regulations (Perda), and to identify factors that hinder its implementation. This study uses an empirical legal approach with qualitative methods. Data were collected through observation, in-depth interviews, and documentation, with the main sources being the Chairman of the DPRD and the Chairman of the Regional Regulation Formation Agency (Bapemperda). The results of the study indicate that the implementation of the legislative function by the DPRD in using the right of initiative has not been running effectively. During the 2019–2024 period, not a single Regional Regulation originated from the DPRD's initiative, out of a total of 27 Perda that have been passed. The DPRD's performance is considered still weak when viewed from public organization performance indicators, namely productivity, service quality, responsiveness, responsibility, and accountability. In addition, there are several inhibiting factors in the implementation of the right of initiative, including limited human resources, internal differences of opinion among DPRD members, the characteristics of the legislative institution as a complex democratic institution, and the busy work schedules of council members. This study recommends improving the capacity of Regional People's Representative Council (DPRD) members to understand the substance of regulations and social dynamics, as well as fostering synergy and collective awareness in carrying out their legislative function. This way, the DPRD's right of initiative can be optimized to produce regulations that are more aspirational and responsive to the needs of local communities.